The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.0001-6349.2005.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Episiotomy and perineal tears presumed to be imminent: the influence on the urethral pressure profile, analmanometric and other pelvic floor findings – follow‐up study of a randomized controlled trial

Abstract: Episiotomy at a perineal tear presumed to be imminent does not have any advantage with regard to pelvic floor function and should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Seven of the 11 studies were carried out in high-income countries, including Canada (Klein 1992), Germany (Dannecker 2004), Ireland (Harrison 1984), Spain (Juste-Pina 2007), and the UK (House 1986; Murphy 2008b; Sleep 1984). Five of the studies were conducted in middle- and low-income countries, and these included Argentina (Belizan 1993), Columbia (Rodriguez 2008), Malaysia (Sulaiman 2013), Pakistan (Ali 2004), and Saudi Arabia (Eltorkey 1994). …”
Section: Resultsmentioning
confidence: 99%
“…Seven of the 11 studies were carried out in high-income countries, including Canada (Klein 1992), Germany (Dannecker 2004), Ireland (Harrison 1984), Spain (Juste-Pina 2007), and the UK (House 1986; Murphy 2008b; Sleep 1984). Five of the studies were conducted in middle- and low-income countries, and these included Argentina (Belizan 1993), Columbia (Rodriguez 2008), Malaysia (Sulaiman 2013), Pakistan (Ali 2004), and Saudi Arabia (Eltorkey 1994). …”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies investigating augmented MUCP were found (Table 1) [14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. One study was excluded because the results combined values for men and women [37].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…When this criterion was applied to women with either SUI or prolapse, between 39 % and 60 % achieved an effective contraction. Furthermore, a number of studies reported a reduction in MUCP during PFM contraction compared with the resting measurement [14,26,32,36]. All of these studies included women with possible injuries to the pelvic floor.…”
Section: Augmentation Of Mucp By Pelvic Floor Contractionmentioning
confidence: 99%
“…Žádná ze studií však nepotvrdila, že by rutinní provádění epiziotomií vedlo ke snížení močové inkontinence u žen po porodu (35,36,37,38,39).…”
Section: Legenda: Ns (Not Significant) -Nesignifikantní Hodnota; or (unclassified